Biomarkers in Cancer 2014
DOI: 10.1007/978-94-007-7744-6_41-1
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 as a Biomarker in Squamous Cell Cancers of the Mouth and Oropharynx

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a malignancy associated with severe mortality despite advances in therapy, and it ranks among the top ten most common cancers worldwide, with a large incidence variation according to sex and geographical location. At the moment, no biomarkers are currently available for HNSCC patients; prognosis depends largely on the stage at presentation, with the most important prognostic factor. Fibroblast growth factor receptors (FGFRs) and ligand binding are among the many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, accumulating evidence suggests that there could be more variability between FGFR4 and other FGFRs than was initially expected. It has been reported that there are a number of amino-acid substitutions in the tyrosine kinase domains of FGFR4 (Dutra et al, 2015;Katoh, 2016). FGF401 (Weiss et al, 2019;Zhou et al, 2019), BLU9931 , and BLU-554 (Hatlen et al, 2019;Kim et al, 2019) have been reported to be the most highly potent and selective FGFR4 inhibitors.…”
Section: Targeting the Fgf19-fgfr4 Pathway Fgfr4 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, accumulating evidence suggests that there could be more variability between FGFR4 and other FGFRs than was initially expected. It has been reported that there are a number of amino-acid substitutions in the tyrosine kinase domains of FGFR4 (Dutra et al, 2015;Katoh, 2016). FGF401 (Weiss et al, 2019;Zhou et al, 2019), BLU9931 , and BLU-554 (Hatlen et al, 2019;Kim et al, 2019) have been reported to be the most highly potent and selective FGFR4 inhibitors.…”
Section: Targeting the Fgf19-fgfr4 Pathway Fgfr4 Inhibitorsmentioning
confidence: 99%
“…FGFR4 has been reported as an oncogenic driver in FGF19positive advanced HCC. A therapeutic strategy against targeting FGF19/FGFR4 is being actively investigated (Dutra et al, 2015;Huynh et al, 2019). Meanwhile, inhibition of FGF19-FGFR4 signaling has been reported to be associated with increased risk of hepatotoxicity and cardiac toxicity (Lin and Desnoyers, 2012).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%